Nursing care for a patient with post-penile prosthesis implantation infection: a case report - Gao, Yan; Zhou, Lina; Wang, Lu; Meng, Wenjun; Liu, Liling; Chen, Huiying; Wang, Yanmei (Frontiers in Surgery, 2025)
BackgroundThree-piece expandable penile prosthesis implantation is the ultimate means to treat penile erectile dysfunction, and patients can achieve high levels of satisfaction. However, once postprosthetic infection occurs, clinical treatment and care become very challenging. However, the nursing experience about this disease is rare reported. Therefore, this paper documents the nursing experience of a single case involving postoperative infection following penile prosthesis implantation, with the objective of providing a reference for the clinical management and nursing care of similar cases.Case summaryWe report the case of a 65-year-old male who developed infection after penile prosthesis surgery. By monitoring the pH value, and temperature and by employing topical probiotics, silver ion dressings, light treatment and other methods used to treat infected wounds, we ultimately assisted the physician in choosing the appropriate wound infection plan for the patient. After 60 days of continuous management, the patient's wound healed. Here, we summarize initiatives for the management of such refractory wounds from a nursing perspective.ConclusionWe summarize the experience in providing nursing care to a patient with a wound infection after penile prosthesis implantation. Our method is very practical and can be applied to similar patients.